Feed your PET - Abuamsha, Yara; Ihbeisheh, Israa (My University, 2017)
Many people travel day by day. But many of them leave something very important alone behind them for too long time .This thing could be a Pet animal! And for looking after this little creature, this system is done. “Feed the pet” System is a Hardware system, which is able to take care of anyone's pet especially when they are away from home. It is a new system that has not been built before, as we found after searching. It is specialized in looking after their food and feed them at scheduled time given by the owner, and with a certain amount. Two types of pets are considered in this system: Cats and Dogs. However, it can be applied to any other type of pets. The system is considered as a car robot. It is a “line-follower” car. This line leads the car to the location of the pet. As mentioned above, the food is given at a given time. Each meal is weighted in order to be more accurate, and then the pet is fed by this meal. The system also supports a feed-back service. More clearly, it communicates with the owner via a GSM system .Each time the meal is provided to each pet, the system sends an SMS message to the owner to inform him about delivering